Pengembangan Media Pembelajaran Flash Card Berbasis Etnomatematika Pengenalan Bangun Datar dan Bangun Ruang pada Siswa Kelas II SDN 235 Bolong Kabupaten Luwu - Nur Asifah; Sukirman Nurdjan; Nilam Permatasari Munir (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to develop ethnomathematics-based flash card learning media on the material of plane and spatial figures for second-grade elementary school students. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 26 second-grade students of SD Negeri 235 Bolong, Luwu Regency. Data collection techniques were carried out through interviews, questionnaires, and tests, while data analysis used quantitative and qualitative descriptive methods. The results of the study showed that the developed ethnomathematics-based flash card media met the criteria of very valid based on the assessment of media experts at 95.83% and material experts at 93.18%. The results of the practicality test obtained a score of 90.2% with a very practical category. In addition, the results of the effectiveness test showed an N-Gain value of 0.81 which is included in the high category. These findings indicate that ethnomathematics-based flash card media is effective in helping students understand the material of plane and spatial figures through contextual and interesting learning.